Level of treatment acceptance in a sample of diabetic patients - kharbachi, mouaadh; bentounes, sadjia (Journal of Social Sciences and Humanities, 2021)
The current study aims to reveal the level of acceptance of treatment among a sample of people with diabetes in a group of educational institutions (secondary level), as well as to identify the differences in acceptance of treatment among the study sample according to the following variables: (gender, marital status, age and type and duration of diabetes). In order to achieve these goals, the research sample selected consisted of 60 patients with diabetes, distributed randomly, using the descriptive approach. A questionnaire was used as a tool to study the acceptance of treatment. The study concluded the following results: The level of treatment acceptance among people with diabetes is high, and there are statistically significant differences in the acceptance of treatment due to gender variables (male, female). Marital status (single, married), age (less than 20 years old, more than 20 years old), and disease category (1st category, 2nd category). As for the variable " duration of diabetes" (less than 5 years, and from